Enhancement of coffee quality in Rwanda: A stakeholder analysis of government policies - Glenn P. Jenkins; Ludovic Mbakop; Mikhail Miklyaev (Queen's University, Department of Economics, 2023)
Over the past two decades, Rwanda has positioned itself as a leading producer of specialty coffee. The shift away from ordinary coffee began in the early 2000s and was buoyed by international donors, NGOs and the government. They all supported the nascent specialty coffee industry by providing a combination of technical assistance and funding to invest in coffee washing stations. Coffee washing stations (CWS) are a pivotal piece of the value chain in Rwanda since it is where ordinary coffee undergoes a process that turn it into specialty coffee. The policy of shifting to specialty coffee has been significantly beneficial to Rwanda. However, there was a rush to build a large number of CWS throughout the country which has resulted in an over capacity of these plants and fierce competition among them for the purchase of cherry coffee from farmers. In an attempt to shore up the industry the Government implemented a zoning policy which effectively is a trade barrier to artificially maintain a high margin between the input price of cherry coffee and the sales price of coffee received by the CWS. This study uses a cost-benefit analysis to estimate the economic welfare loss to Rwanda of these policies. Over a ten year period the present value of the economic loss is estimated to be 73 million. An increased competition in the market for cherry coffee would raise the price of cherry coffee at the expense of the profits of CWS owners. If such a policy were implemented coffee growers could potentially receive up to 150% more from their sales of cherry coffee, or 45 million per year. These enhanced revenues would allow famers to finance the replanting of their coffee fees and maintain the sustainability of this sector.
Keywords: D40; E23; Q17; 330; Coffee value chain; coffee washing station; specialty coffee; coffee zoning policy